A Current–Voltage Model for Double Schottky Barrier Devices. (28th December 2020) - Grillo, Alessandro; Di Bartolomeo, Antonio
Abstract: Schottky barriers (SBs) are often formed at the semiconductor/metal contacts and affect the electrical behavior of semiconductor devices. In particular, SBs are playing a major role in the investigation of the electrical properties of mono and 2D nanostructured materials, although their impact on the current–voltage characteristics is frequently neglected or misunderstood. In this work, a single equation is proposed to describe the current–voltage characteristics of two‐terminal semiconductor devices with Schottky contacts. The equation is applied to numerically simulate the electrical behavior for both ideal and nonideal SBs. The proposed model can be used to directly estimate the SB height and the ideality factor. It is applied to perfectly reproduce the experimental current–voltage characteristics of ultrathin molybdenum disulfide or tungsten diselenide nanosheets and tungsten disulfide nanotubes. The model constitutes a useful tool for the analysis and the extraction of relevant transport parameters in any two‐terminal device with Schottky contacts. Abstract : A model consisting of a single equation and allowing easy parameter extraction is proposed to describe the current–voltage characteristics of two‐terminal semiconductor devices with Schottky contacts. The model is successfully applied to ultrathin MoS2, WSe2 and WS2 nanodevices.